2018
DOI: 10.1002/rhc3.12142
|View full text |Cite
|
Sign up to set email alerts
|

Creating Emergency Prepared Households—What Really Are the Determinants of Household Emergency Preparedness?

Abstract: We draw on social capital and social vulnerability explanations to investigate the determinants of household emergency preparedness using data from the 2008 General Social Survey (GSS) and multivariate ordinal logistic regression. We develop an ordinal-level scale for household emergency preparedness. We also create indices for individual social capital and risk perception, which correlate with higher levels of household emergency preparedness. We show that race and gender per se do not make households more or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 61 publications
1
39
1
1
Order By: Relevance
“…1 Within the preparedness literature, individuals who consistently yielded higher levels of predisaster preparedness included: older adults, those with higher levels of education, higher income, homeowners, those of specific religious affiliations, those with higher levels of social support, and military veterans. [2][3][4][5][6][7][8][9][10][11][12] Conversely, individuals identified as least prepared within the literature included: racial/ethnic minorities, the medically fragile, the disabled, those with inadequate social support, the mental ill, those with low literacy levels, and those responsible for extended family members. 2,3,6,11,[13][14][15][16][17][18][19][20][21] However, past studies showed inconsistent results on how gender, the presence of children, and prior disaster experience influenced levels of preparedness.…”
mentioning
confidence: 99%
“…1 Within the preparedness literature, individuals who consistently yielded higher levels of predisaster preparedness included: older adults, those with higher levels of education, higher income, homeowners, those of specific religious affiliations, those with higher levels of social support, and military veterans. [2][3][4][5][6][7][8][9][10][11][12] Conversely, individuals identified as least prepared within the literature included: racial/ethnic minorities, the medically fragile, the disabled, those with inadequate social support, the mental ill, those with low literacy levels, and those responsible for extended family members. 2,3,6,11,[13][14][15][16][17][18][19][20][21] However, past studies showed inconsistent results on how gender, the presence of children, and prior disaster experience influenced levels of preparedness.…”
mentioning
confidence: 99%
“…Extant scholarship suggests that because preparing emergency plans requires the involvement and commitment of many organizations and their personnel (Andrew & Carr, 2013), confidence in such plans should be associated with coordination effectiveness. Emergency management plans include response instructions, guidelines, templates, and forms to help promote and coordinate preparedness and assist in the response protocols to improve response and recovery in case of an emergency (Nukpezah & Soujaa, 2018). Contrary to expectations, the existence of such plans is not statistically related to coordination effectiveness that professionals perceive.…”
Section: Resultsmentioning
confidence: 99%
“…Although the emergency management scholarship investigates social capital as a sociological phenomenon that contributes to household and community emergency preparedness (Nukpezah and Soujaa, 2018;Kapucu and Garayev, 2016;Reininger et al, 2013;Uscher-Pines et al, 2013;Magsino, 2009;Nakagawa and Shaw, 2004;Putnam, 1995), the extant scholarship studies social capital as trust relations or access to collective resources at either the individual or collective level (Nukpezah and Soujaa, 2018;Kawachi et al, 1997). However, what is considered a valuable social capital should depend on individual goals and needs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rather than study social capital only as a causal variable in empirical studies, it should also be investigated as an outcome variable and its determinants examined (Feinstein and Hammond, 2004;Narayan and Cassidy, 2001). Although recent studies examine how social capital, operationalised at the individual level, contributes to disaster response and preparedness (Nukpezah and Soujaa, 2018;Bhandari, 2014), scant theoretical framework exists within the emergency management scholarship for thinking about the determinants of ISCEP. The present study surmises that this lack of research limits the avenues through which goal specific individual social capital accumulations improve societal outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation